THE RELATIONSHIP BETWEEN KNOWLEDGE LEVEL, SOCIOECONOMIC LEVEL AND HUSBAND'S SUPPORT FOR COMPLETENESS OF BASIC IMMUNIZATION FOR BABIES AT POSYANDU TIARA, CIBODAS BARU VILLAGE IN 2023 - Triyana, Anisa; Madhena, Melisa Putri Rah (HEARTY, 2024)
Background: Immunization is a very effective health strategy for reducing the mortality rate of newborns and children. 2018 Basic Health Research data shows that Complete Basic Immunization (IDL) coverage reached 57.9% and for incomplete immunization it was 32.9% and 9.2%. Objective: To determine the relationship between mother's level of knowledge, socio-economic level, and husband's support for the completeness of basic immunization for babies at Posyandu Tiara, Cibodas Baru Village in 2023. Method: This research design used a cross sectional with a questionnaire method with a sample size of 72 respondents with the criteria of mothers having children aged > 1 year at Posyandu Tiara with chi-square α=0.05. Results: The results of the study show that there is a significant relationship between level of knowledge (p= 0.002), husband's support (p= 0.004) and there is no significant relationship between socio-economic level (p= 0.060). Conclusion: the completeness of basic immunization for babies at Tiara Posyandu means that the number of mothers who have babies is 72, with incomplete immunization results for their children being 22 (30.6%) while those with complete basic immunization for their children are 50 (69). 4%) respondents. Suggestion: Posyandu cadres need to make efforts to ensure mothers take their babies to the posyandu and monitor the completeness of basic immunizations for babies.